Correlation Between HIV Rapid Test and HIV Viral Load in HIV Patients at Haji Hospital in Surabaya - Resty Cahya Pertiwi; Evy Diah Woelansari; Ayu Puspitasari (International Journal of Advanced Health Science and Technology, 2023)
HIV (Human Immunodeficiency Virus) is a virus that causes decreased immunity. Examinations that can be done for HIV testing include a rapid HIV test and HIV viral load. The rapid HIV test is a test that is used to find out the antibodies in the sample, while the viral load test is to find out the amount of HIV. The purpose of this study was to compare HIV using a rapid test with HIV viral load in people with HIV. This type of research is observational with a cross-sectional approach. The sample in this study were 30 samples from HIV sufferers who carried out an HIV viral load examination using the Molecular Rapid Test (TCM) method at the RSUD Haji Provinsi Jawa Timur, then a rapid HIV test was carried out using the immunochromatography method. The results of the HIV rapid test and HIV viral load were processed in the form of a bar chart and tested with the McNemar statistical test. The results of the McNemar test can be concluded that there is a significant difference between the results of the HIV viral load examination of HIV viral load by the Molecular Rapid Test (TCM) method is superior to the HIV rapid test. However, rapid tests can be used in diagnosing HIV infection.